Nonreciprocal superconductivity at Ti2O3/GaN interface - Peng Dong; Lijie Wang; Guanqun Zhang; Zhongfeng Ning; Jiadian He; Yiwen Zhang; Yifan Ding; Xiaohui Zeng; Yanjiang Wang; Jinghui Wang; Xiang Zhou; Yueshen Wu; et al. (APL Quantum)
Two-dimensional superconductors exhibit intriguing quantum physical phenomena and hold promising potential for superconducting circuit applications due to their inherently broken inversion symmetry, which can introduce additional degrees of freedom related to spin or momentum. Achieving chemical stability in atomic layer 2D superconductors, including mechanical exfoliation and film deposition, remains both fundamentally and technologically challenging. Naturally, interfacial superconductivity, enclosed and safeguarded between two materials, is considered an ideal two-dimensional candidate, providing a stable and immaculate platform to explore correlated phenomena with inversion symmetry breaking in the 2D limit. Here, we report a Rashba spin–orbit coupling induced momentum-dependent superconducting order parameter in the inversion symmetry breaking heterointerface superconductor Ti2O3/GaN. Remarkably, nonlinear responses emerge in the superconducting transition regime when the magnetic field is precisely aligned parallel to the interface and perpendicular to the applied current. In particular, the observed nonreciprocal supercurrent is extremely sensitive to the direction of the field for 0.5°, suggestive of a crossover from a symmetry breaking state to a symmetric one. Our finding unveils the underlying rich physical properties in heterointerface superconductors, providing an exciting opportunity for the development of novel mesoscopic superconducting devices.